Comparison of parental estimate of developmental age with measured IQ in children with neurodevelopmental disorders. (28th April 2016) - Chandler, S.; Howlin, P.; Simonoff, E.; Kennedy, J.; Baird, G.
Summary: Background: Formal IQ tests are an important part of the diagnostic and needs‐based assessment process for children with neurodevelopmental disorders. However, resources for such assessments are not always available. It has been suggested that parental estimates of their child's developmental age could serve as a proxy IQ when formal measures are unavailable. Method: Parental estimates of their child's developmental age were converted to a developmental quotient (DQ) in 197 children with Autism Spectrum Disorder (ASD) aged 4–9 years, and 108 children with ADHD and intellectual disability (ADHD + ID) aged 7–15 years. Formal IQ assessments were then conducted. Parents completed the Social Communication Questionnaire ((SCQ), a measure of autism symptomatology) and a demographic questionnaire. Results: In the ASD sample, 58% of parent estimates were within 15 points (i.e. one standard deviation) of the child's measured IQ score. Lower measured IQ and lower SCQ total score predicted higher parental accuracy. In the ADHD + ID sample, 74% of parental estimates were within 15 points of measured IQ. In this group, higher child IQ predicted greater parental accuracy. Parents in the ADHD + ID group were more likely to overestimate children's ability level than parents in the ASD group. Conclusions: In this study, the majority of parents of children with ADHD and ID were able to estimate their child's intellectual ability level with some accuracy. Parents of children with ASD were less accurate, but this may be because these parents were focussing more on children's level of adaptive functioning, which is known to be typically lower than cognitive ability in ASD.